8‐acetoxy‐trisulfopyrene as the first activatable fluorogenic probe for add‐and‐read assessment of Organic anion‐transporting polypeptides, OATP1B1, OATP1B3, and OATP2B1. Issue 9 (19th August 2021) - Ungvári, Orsolya; Király, Laura; Bakos, Éva; Özvegy‐Laczka, Csilla
Abstract: Organic anion‐transporting polypeptides, OATP1B1, OATP1B3, and OATP2B1 are multispecific membrane proteins mediating the hepatocellular uptake of structurally diverse endo‐ and exogenous compounds, including various kinds of drugs. Co‐administration of OATP1B/2B1 substrates may lead to altered pharmacokinetics or even toxicity. Therefore, the study of the interaction with these OATPs is essential in drug development and is recommended by international regulatory agencies, the FDA, EMA, and PMDA. In general, radiolabeled indicators are used to measure drug interactions of OATPs, and, lately, fluorescent probes are also gaining wider application in OATP tests. However, all of the currently available methods (either radioactive or fluorescence‐based) comprise multiple steps, including the removal of the indicator in the end of the experiment. Hence, they are not ideally suited for high‐throughput screening. In the current study, in order to find an indicator allowing real‐time assessment of hepatic OATP function, we searched for an activatable fluorogenic OATP substrate. Here, we show that 8‐acetoxypyrene‐1, 3, 6‐trisulfonate (Ace), a fluorogenic derivative of the hepatic OATP substrate pyranine (8‐hydroxypyrene‐1, 3, 6‐trisulfonate) enters the cells via OATP1B1/3 or OATP2B1 function. In living cells, Ace is then converted into highly fluorescent pyranine, allowing "no‐wash" measurement of OATP function and drug interactions. Furthermore, we demonstrate that Ace can be used in an indirect assay termed as competitive counterflow suitable to distinguish between transported substrates and inhibitors of OATP1B1. The fluorescence‐based methods described here are unique and open the way toward high‐throughput screening of interactions between new molecular entities and OATPs.